Modern analytic philosophy: historical origins and prospects of development. (Based on the materials of the 11th International Congress of the Society for Analytical Philosophy, September 12-15, 2022, Berlin, Germany) - Shramko, Yaroslav; Khomenko, Iryna (Sententiae, 2022)
Review of materials of the 11th International Congress of the German Society for Analytical Philosophy, as well as the latest trends in the development of analytical research.